Next-generation sequencing platforms for latest livestock reference genome assemblies - Gatew, H.; Mekuriaw, Getinet (Academic Journals, 2018)
Next-generation sequencing (NGS) or high-throughput sequencing platforms refers to different modern sequencing technologies that allow scientist to sequence millions to billions of reads (base pairs) in a single, much more quicker and cheaper cost than the previously used Sanger (first generation) sequencing method. Next-generation sequencing platforms classified as second generation sequencing platforms which require polymerase chain reaction (PCR) amplification and third generation sequencing platforms which do not require PCR amplification for sequence. The appearance of next generation sequencing technologies has revolutionized the genome sequencing of organisms including farm animals. These platforms enable scientists to access latest and detailed information about genetic markers that are responsible for economically important traits. Identification of candidate genes responsible for these traits in different species can bring down the overall cost of livestock breeding by improving productivity and disease resistance. Even though the output and error rate of third generation sequencing platforms (Pacific Biosystems and Nanopore) remain to be improved, they offered long read length relatively with cheaper sequencing cost and easy sample preparation. Oxfored NanoporeMinION devices are the most portable third generation DNA sequencer available in the size of a small cell phone that can be plugged into the USB of a laptop.